Exploring the Dominance of Literature in English Studies, Its Consequences and Implications: A Reader-Response Analysis - Tamang, Hira Man (Journal of NELTA Karnali, 2024)
This article explores the reasons behind the dominance of literature in English Studies (ES), its history, consequences and future direction. Applying David Bleich’s subjective reader-response theory, this literary research studies secondary resources; books, book chapters and articles. Both literature and language were studied as an English subject. Later language was separated from English Studies creating its field like linguistics. Both disciplines remained incomplete due to the separation. Gradually, literature became de-textual and language became de-contextual. Now it is the time to reunite both of them and make the powerful discipline again making it an inter-disciplinary study. Although many attempts have been made to combine both disciplines; language and literature, the education system, politics, curriculum, and government funding affect it. This study gives the ideas of developing and implementing an interdisciplinary English curriculum to curricularists, educators, and teachers and empowers students with theoretical understanding and practical skills. Empirical studies can be carried away by collecting primary data in future.